2022
DOI: 10.1007/s00417-022-05551-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripapillary vascular flow in patients with Thyroid-Associated Ophthalmopathy (TAO) by OCT Angiography

Abstract: Purpose To evaluate changes in peripapillary vascular blood flow indices (PVBFI) in patients with thyroid-associated ophthalmopathy (TAO) using OCT angiography (OCTA) technology. Methods Patients with TAO and control subjects matched for age and sex were included in the study. Eye examination, Clinical Activity Score (CAS) evaluation and OCTA scan analysis (Topcon ImageNet 6; DRI OCT Triton, Topcon Corporation) were performed. In particular, PVBFI of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…OCTA, a novel noninvasive technique, was recently adopted to quantitatively measure retinal and choroidal microvasculature in different ocular and systemic diseases, such as glaucoma (27,28), age-related macular degeneration (29-31), optic neuropathies (32-35), leukemia (36), diabetic retinopathy (37)(38)(39)(40), and TAO (14,19,20,41,42), and to evaluate the severity and prognosis of these diseases. Our study showed that the macular retinal VD was significantly decreased in the ODE and NODE groups compared with the normal group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCTA, a novel noninvasive technique, was recently adopted to quantitatively measure retinal and choroidal microvasculature in different ocular and systemic diseases, such as glaucoma (27,28), age-related macular degeneration (29-31), optic neuropathies (32-35), leukemia (36), diabetic retinopathy (37)(38)(39)(40), and TAO (14,19,20,41,42), and to evaluate the severity and prognosis of these diseases. Our study showed that the macular retinal VD was significantly decreased in the ODE and NODE groups compared with the normal group.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography angiography (OCTA), a noninvasive and quantitative technique, has been used to evaluate retinal and choroidal microvascular density (VD) in TAO patients (12)(13)(14)(15)(16)(17) and has been used to diagnose and monitor the early stage of vision-threatening TAO (18)(19)(20)(21). Our previous study on OCTA reported that the vessel density (VD) of the retinal macula and radial peripapillary capillaries (RPCs) was decreased in CRF patients compared with TAO patients without CRFs (11).…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Del Noce et al, there was a significant decrease in the peripapillary choriocapillaris and deep capillary plexus VD in patients with TED compared to healthy age and gender-matched controls. The study demonstrates a significant relationship between higher CAS scores and lower peripapillary choriocapillaris VD [ 19 ]. These studies showed significant alteration in ONH VD in patients with higher CAS scores like ours.…”
Section: Discussionmentioning
confidence: 99%
“…The same autoimmune disorder that causes Graves’ orbitopathy also attacks thyroid gland resulting in thyroid overactivity (hyperthyroidism) also called Graves’ disease [50]. On OCTA, Ye et al [51] demonstrated that there is increased retinal microvascular density in patients with active TED compared with controls, which also correlated with visual acuity while in the recent study of del Noce et al [52 ▪▪ ] peripapillary blood flow indices were lower in TED patients in both deep capillary plexus and choriocapillaris layers with the latter being correlated with disease activity. Furthermore, decrease in peripapillary and macular vascular density as well as increase in RNFL thickness are noted in active TED compared with inactive TED and healthy eyes [53 ▪ ].…”
Section: Introductionmentioning
confidence: 98%